2021
DOI: 10.3390/cancers13020175
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Radiotherapy Impact on Late Bladder Toxicity in Prostate Cancer Patients: An Observational Study

Abstract: Background and purpose: The aim of our study was to elaborate a suitable model on bladder late toxicity in prostate cancer (PC) patients treated by radiotherapy with volumetric technique. Materials and methods: PC patients treated between September 2010 and April 2017 were included in the analysis. An observational study was performed collecting late toxicity data of any grade, according to RTOG and CTCAE 4.03 scales, cumulative dose volumes histograms were exported for each patient. Vdose, the value of dose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In the era of personalized medicine, it is increasingly important to be able to predict toxicity and response to radiation treatment through radiomics and dosimetric parameters [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of personalized medicine, it is increasingly important to be able to predict toxicity and response to radiation treatment through radiomics and dosimetric parameters [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving an AUC of ≥ 0.6 and having a minimum 95 % CI ≥ 0.5 were considered statistically significant by Gulliford et al [23] . Internal validation was accomplished using bootstrapping techniques to obtain the best fit predictors with associated 95 % CI as described in published studies [24] , [25] . Lastly, subgroup analysis was conducted on MVA predictors using the AUC curve to determine the most relevant threshold differentiating the defined toxicity [26] .…”
Section: Methodsmentioning
confidence: 99%
“…This could be caused by data imbalance due to fewer toxicity events or LKB-NTCP as the dosimetric variable might not be the only driver of late GU toxicity. Studies have suggested that the inclusion of clinical predictors have improved the overall model performance for the defined GU toxicity (24,38).…”
Section: Lkb-ntcp Parameters For Grade ≥2 Gu Toxicitymentioning
confidence: 99%
“…Additionally, different rectal and bladder complications might be the results of various rectal/bladder pathogenic mechanisms as the existing constructed biological models were based on some assumptions and do not consider all involved biological mechanisms (42). Moreover, risk and severity of GI and GU toxicities have been reported to be associated with other factors such as patient's characteristics, hormonal therapy and the intake of medications (38,43,44). Thus, applications of the recommended LKB-NTCP parameters should include similar scenarios to those which the parameters were derived to have a more reliable toxicity estimation (45).…”
Section: Lkb-ntcp Parameters For Grade ≥2 Gu Toxicitymentioning
confidence: 99%